Maxillofacial Trauma and Psychological Stress - Young Cecilia; Yeung CYYJ (Journal of Medical and Psychological Trauma, 2018)
A review links maxillofacial trauma to psychological stress responses. It discusses screening, early interventions, and multidisciplinary care to improve recovery.